The Impact of On-Ground Activation Events on Improved Toilet Coverage: A Case Study From the Tanzania National Sanitation Campaign "" - Joshua Mwakalikamo; Emili Sankwa; Robert Aunger (SAGE Publishing, 2023)
In 2017, Tanzania was one of the countries in the world with the lowest proportion of households having access to improved toilets. Between 2017 and 2021, the government launched a national sanitation campaign under the brand Nyumba ni Choo . The objective of this paper is to assess the impact of one component of this campaign, "direct consumer contact" events, on the coverage of improved household latrines in Tanzania. Secondary data from both the National Sanitation Management Information System (NSMIS; https://nsmis.moh.go.tz/ ) and internal project reports were used to extract data on coverage and dates of events, respectively. Regression estimation models were used to estimate impact at ward and regional levels. The study used quarterly panel data from all 26 regions between 2017 (baseline) and 2020 (endline) for estimation purposes. The study shows that direct consumer contact events had a significant positive effect on the rate at which households subsequently improved their toilets at both small and large scale in Tanzania. On average, the rate of household latrine improvement increased by 12.91% at ward level and 14.17% at regional level. These results testify to the importance of designing an effective behavioral change campaign to achieve significant improvements in sanitation coverage.